Survey on Routing in Pocket Switched Network - Sarkar, Ratna R.; Rasul, Khadija; Chakrabarty, Amitabha (Scientific Research Publishing, 2015)
Pocket switched Network (PSN) is an emerging research magnet that has been attracting researchers. This paper provides an introduction to PSN and covers some of its basic features and challenges. Continuous connectivity is difficult in infrastructure independent communication. In this paper, we will see how PSN provides an effective alternative. We also explain some routing protocols that can be incorporated for effective data forwarding. This paper also discusses possible applications and areas where PSN can be effectively used and some ideas that may foster future research in PSN routing.
Keywords: Pocket Switched networks; Connectivity; PSN Routing protocols; Forwarding